2023
DOI: 10.1093/gerona/glad138
|View full text |Cite
|
Sign up to set email alerts
|

Frailty Resilience Score: A Novel Measure of Frailty Resilience Associated With Protection From Frailty and Survival

Abstract: Frailty is characterized by increased vulnerability to disability and high risk for mortality in older adults. Identification of factors that contribute to frailty resilience is an important step in the development of effective therapies that protect against frailty. First, a reliable quantification of frailty resilience is needed. We developed a novel measure of frailty resilience, the Frailty Resilience Score (FRS), that integrates frailty genetic risk, age, and sex. Application of FRS to the LonGenity cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Although we previously demonstrated that a Frailty Index that uses standard clinical and HrQoL measures is helpful in the South Texas population ( 1 ), what is novel is that the HrQoL measures, more than the biological measures of health, are the best predictors of frailty. Frailty is a state of increased vulnerability to disproportionate change in health due to the accumulation of small damages ( 35 ) and is linked to increased falls, hospitalizations, morbidity, mortality, and reduced quality of life ( 29 ). Resilience to frailty includes physical, genetic, social, and psychological moderators ( 2 , 4 , 26–28 , 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we previously demonstrated that a Frailty Index that uses standard clinical and HrQoL measures is helpful in the South Texas population ( 1 ), what is novel is that the HrQoL measures, more than the biological measures of health, are the best predictors of frailty. Frailty is a state of increased vulnerability to disproportionate change in health due to the accumulation of small damages ( 35 ) and is linked to increased falls, hospitalizations, morbidity, mortality, and reduced quality of life ( 29 ). Resilience to frailty includes physical, genetic, social, and psychological moderators ( 2 , 4 , 26–28 , 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study of community-dwelling older adults demonstrated statistically significant negative associations between physical frailty, psychological frailty, and all dimensions of HrQoL (25). Conversely, resilience is associated with protection from frailty (2,4,(26)(27)(28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%